2018
DOI: 10.1002/lno.10823
|View full text |Cite
|
Sign up to set email alerts
|

Season‐specific trends and linkages of nitrogen and oxygen cycles in Chesapeake Bay

Abstract: A three‐decade time series of solute concentrations was combined with a box‐modeling system to analyze long‐term trends in the concentration, production, and transport of dissolved inorganic nitrogen species along the mainstem axis of Chesapeake Bay. Water‐ and salt‐balance calculations associated with box‐modeling provided regional, seasonal, and interannual estimates of net advective and nonadvective transport and net biogeochemical production rates for oxygen and dissolved nitrogen. The strongest decadal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 73 publications
3
37
0
Order By: Relevance
“…They attributed this to a 23% decline in dissolved nitrogen concentrations. Testa et al (2018) reported a decline in NH 4 and an increase in NO 2+3 concentrations in channel bottom waters during late summer as dissolved oxygen concentrations have increased, suggesting a vicious biogeochemical cycle may be breaking (Kemp et al, 2005). Zhang et al (2018) demonstrated progressive improvement in a multimetric index of water quality attainment that integrates dissolved oxygen, water clarity, submersed vascular vegetation and chlorophyll a.…”
Section: Chesapeake Baymentioning
confidence: 99%
“…They attributed this to a 23% decline in dissolved nitrogen concentrations. Testa et al (2018) reported a decline in NH 4 and an increase in NO 2+3 concentrations in channel bottom waters during late summer as dissolved oxygen concentrations have increased, suggesting a vicious biogeochemical cycle may be breaking (Kemp et al, 2005). Zhang et al (2018) demonstrated progressive improvement in a multimetric index of water quality attainment that integrates dissolved oxygen, water clarity, submersed vascular vegetation and chlorophyll a.…”
Section: Chesapeake Baymentioning
confidence: 99%
“…November had a very low ratio, potentially related to coupled denitrification and nitrification, which are at maximum rates during the fall ( McCarthy et al, 1984;Kemp et al, 1990;Lee et al, 2015;Testa et al, 2018) and is positively correlated with suspended particles as in the ETM (Damashek et al, 2016). Given the non-conservative behavior of inorganic carbon in this region, and minimal buffering resulting in relatively large changes in conditions with changes in the carbonate parameters, higher resolution study is needed, particularly given the lack of measurements within the flats area, the potential for nitrogenrelated effects on alkalinity, and the analytical complications associated with the periodic presence of the ETM.…”
Section: Non-conservative Alkalinity In the Upper Baymentioning
confidence: 99%
“…The adaptation to estuarine environments could also be demonstrated in variations of bacterial production, respiration, and growth efficiency in estuaries (Shish and Ducklow 1994). For instance, recent urbanization and other anthropogenic activities have increased nitrogen (N) and phosphorous (p) loadings and stimulated increase of net primary productivity and high rates of microbial metabolism (Zhou et al 2014;Testa et al 2018). Taken together, these physiological adaptations create a unique spatial and temporal distribution and dynamic balance of microbial populations in estuarine environments.…”
mentioning
confidence: 99%